2016
DOI: 10.1586/1744666x.2016.1144473
|View full text |Cite
|
Sign up to set email alerts
|

SQ house dust mite (HDM) SLIT-tablet provides clinical improvement in HDM-induced allergic rhinitis

Abstract: House dust mite (HDM) allergy represents a highly prevalent inhalant allergy, and exposure to HDM allergens results in allergic rhinitis with persistent symptoms that may not be adequately controlled with available allergy pharmacotherapy. Allergy immunotherapy constitutes a complementary treatment option targeting the underlying immunological mechanisms of allergic disease and represents the only treatment with a potential for disease modification and long-term efficacy. As traditional allergy immunotherapy d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 62 publications
(96 reference statements)
1
13
0
Order By: Relevance
“…Although a review46 of studies found no consensus on basic treatment parameters and questioned the efficacy of SLIT, a considerable number of our included studies support our results. Moreover, multiple systematic reviews474849 have resulted in recommendations for the use of SLIT in the management of perennial AR. The author of a recent review49 also highlighted evidence supporting the efficacy of SLIT in the management of allergic respiratory diseases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although a review46 of studies found no consensus on basic treatment parameters and questioned the efficacy of SLIT, a considerable number of our included studies support our results. Moreover, multiple systematic reviews474849 have resulted in recommendations for the use of SLIT in the management of perennial AR. The author of a recent review49 also highlighted evidence supporting the efficacy of SLIT in the management of allergic respiratory diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, SLIT tablet studies are associated significantly with symptom relief and decreased rescue medication use in PAR. Unfortunately, the number of SLIT tablet studies is limited (n=6), so the efficacy of SLIT tablets requires further verification in additional, larger clinical trials, as suggested by others 4648…”
Section: Discussionmentioning
confidence: 99%
“…While the efficacy of specific allergen immunotherapy and, even more, sublingual immunotherapy (SLIT) were previously disputed 7 , a change of paradigms has taken place with the increasing number of controlled clinical trials conducted in HDM allergy patients using various formulations of HDM SLIT, such as tablets or drops. The clinical efficacy and long-term effects of HDM SLIT in AR is today undisputable in adults in European 8, 9 and US 10 studies, as well as in elderly patients 11 and in children 12–15 .…”
Section: Introductionmentioning
confidence: 99%
“…For patients suffering from multiple manifestations of HDM-induced respiratory allergic disease, the SQ HDM SLITtablet may constitute a particularly relevant treatment option. As mentioned, in addition to clinical data reviewed in this Drug Profile demonstrating significant clinical improvement in HDM allergic asthma, treatment with the SQ HDM SLITtablet has been found to significantly improve disease control in HDM allergic rhinitis, as observed by patients reporting lower symptom scores, decreased allergy pharmacotherapy use, and an improved quality of life [51]. This observed effect on several disease manifestations reflects the advantage of targeting underlying immunological mechanisms of HDMinduced respiratory allergic disease.…”
Section: Expert Commentary and Five-year Viewmentioning
confidence: 83%
“…Clinical efficacy in HDM allergic rhinitis has been demonstrated in several randomized, double-blind, placebo-controlled trials conducted in Europe, as reviewed recently by Klimek et al [51], and in phase III trials in North America and in Japan.…”
Section: Phase II and Phase Iii Studiesmentioning
confidence: 93%